If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 440 + (2x + 20) + (2x + 20) = 900 Reorder the terms: 2x + 440 + (20 + 2x) + (2x + 20) = 900 Remove parenthesis around (20 + 2x) 2x + 440 + 20 + 2x + (2x + 20) = 900 Reorder the terms: 2x + 440 + 20 + 2x + (20 + 2x) = 900 Remove parenthesis around (20 + 2x) 2x + 440 + 20 + 2x + 20 + 2x = 900 Reorder the terms: 440 + 20 + 20 + 2x + 2x + 2x = 900 Combine like terms: 440 + 20 = 460 460 + 20 + 2x + 2x + 2x = 900 Combine like terms: 460 + 20 = 480 480 + 2x + 2x + 2x = 900 Combine like terms: 2x + 2x = 4x 480 + 4x + 2x = 900 Combine like terms: 4x + 2x = 6x 480 + 6x = 900 Solving 480 + 6x = 900 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-480' to each side of the equation. 480 + -480 + 6x = 900 + -480 Combine like terms: 480 + -480 = 0 0 + 6x = 900 + -480 6x = 900 + -480 Combine like terms: 900 + -480 = 420 6x = 420 Divide each side by '6'. x = 70 Simplifying x = 70
| b^2+8b+16= | | 5x-6+4(2x+3)= | | 20x-1=17x+40 | | 6x+8y=47 | | (-110)+6x=-74 | | X-5x+20=10 | | 2w+9.4=39.8 | | -2x+11=15 | | 5r=2r-3 | | 7n-8+5k-4n+4k= | | (-110)+6x=74 | | -8v+36=-2v | | 5r-1=2r-2 | | 5(3+4x)=-13(1-x) | | 6k+5-4k+10= | | 16-2(u+9)=6u+40 | | 2(4x+11)+(4x+11)=195 | | f(-3)=6x^2-x-2 | | 5a+2b+3a+8+6b= | | 10y+16=2(5y+8) | | x=1.5+2.5y | | x=1.5+2.5 | | log(x+5)-log(x+2)=5 | | 3(y+1)+-1(y+5)=4y-6 | | 15p+1q-5q+90= | | 1.9x+37.44=1.3x | | 11(5+x)=-99 | | 6X+14.6=24 | | 7=1xw | | 15q+1q-5q+90= | | -2x+1=-4+9 | | -13=5+20-2m |